Investigation on morphological properties of In2S3 by high pressure x-ray diffraction. (3rd August 2017) - Li, Yuqiang; Wang, Qinglin; Gao, Yang; Liu, Bao; Gao, Chunxiao; Ma, Yanzhang
Abstract: In2 S3 has been investigated under pressures up to 41.3 GPa at room temperature by in situ angle dispersive synchrotron x-ray diffraction in a diamond anvil cell. In the studied pressure range, the diffraction pattern can be indexed into the face centered tetragonal structure. No evident structural phase transition can be determined even with the emergence of some peaks, which can be considered as from impurity. The bulk modulus is determined to be K 0   =  37.8  ±  0.2 GPa with K ′  =  4.44  ±  0.05. In addition, we have documented a difference in the compressibility around two experiments associated with different pressure transmitting medium.